Effect of HPV on head and neck cancer patient survival, by region and tumor site: A comparison of 1362 cases across three continents. (November 2016) - D'Souza, Gypsyamber; Anantharaman, Devasena; Gheit, Tarik; Abedi-Ardekani, Behnoush; Beachler, Daniel C.; Conway, David I.; Olshan, Andrew F.; Wunsch-Filho, Victor; Toporcov, Tatiana N.; Ahrens, Wolfgang; Wisniewski, Kathy; Merletti, Franco; et al.
Highlights: HNSCC survival was poorer among cases in Brazil than in the US and Europe. HPV+/p16+ OPSCC predicted lower mortality in all 3 regions (US, Europe, Brazil). HPV was not prognostic among non-OP HNSCC (OC, larynx, and HP). Effect of HPV/p16 was significantly different in OPSCC & non-OP HNSCC. Abstract: Objectives: To explore whether HPV-related biomarkers predict oropharyngeal squamous cell cancer (OPSCC) survival similarly across different global regions, and to explore their prognostic utility among non-oropharyngeal (non-OP) head and neck cancers. Methods: Data from 1362 head and neck SCC (HNSCC) diagnosed 2002–2011 was used from epidemiologic studies in: Brazil (GENCAPO study, n = 388), U.S. (CHANCE study, n = 472), and Europe (ARCAGE study, n = 502). Tumors were centrally tested for p16 INK4a and HPV16 DNA (by PCR). Risk of mortality was examined using Cox proportional hazard models. Results: There were 517 OPSCC and 845 non-OP HNSCC. Cases were primarily male (81%), ever smokers (91%), with median age of 58 years and median follow-up of 3.1 years (IQR = 1.4–5.9). Among OPSCC, the risk of mortality was significantly lower among 184 HPV-related (i.e., p16+/HPV16+) compared to 333 HPV-unrelated (p16- and/or HPV16-) cases (HR = 0.25, 95%CI = 0.18–0.34). Mortality was reduced among HPV-related OPSCC cases from the U.S., Europe, and Brazil (each p ⩽ 0.01) and after adjustment, remained significantly reduced (aHR = 0.34, 95%CI = 0.24–0.49). Among non-OP HNSCC, neither p16 (aHR = 0.83, 95%CI = 0.60–1.14), HPV16 DNA (aHR = 1.20, 95%CI = 0.89–1.63), or p16+/HPV16+ (aHR = 0.59, 95%CI = 0.32–1.08) was a significantly predictor of mortality. When interaction was tested, the effect of HPV16/p16 was significantly different in OPSCC than non-OP HNSCC (p-interaction = 0.02). Conclusion: HPV-related OPSCCs had similar survival benefits across these three regions. Prognostic utility of HPV among non-OP HNSCC is limited so tumor HPV/p16 testing should not be routinely done among non-OP HNSCC.